Correspondence of hydrobiological and microbiological parameters in the water quality assessment of the middle course of the Misoča River (Annals of the Institute of Biology, 2022)
The water quality of the Misoča River was analyzed on two sites of the middle course, in a populated and in an unpopulated area. The research included sampling of macrozoobenthos and water for microbiological analysis, identification of macrozoobenthos taxa, application of hydrobiological indices for water quality assessment and microbiological analysis of water quality. The goal was to determine the compatibility and complementarities of different aspects of water quality analysis, and to demonstrate the expediency of a multi-aspect and multi-disciplinary approach for this type of research. Through this, an assessment of the water quality of a selected part of the Misoča River, which is very important for the water supply of the surrounding area, was carried out. According to the results of the macrozoobenthos analysis and the applied diversity and water quality indices, the Misoča River belongs to the β-mesosaprobic category, which indicates moderate pollution. The results of the analysis of microbiological parameters also indicate moderate pollution.